2016
DOI: 10.1016/j.midw.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the needs, concerns and knowledge of women diagnosed with gestational diabetes: A qualitative study

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 23 publications
6
86
1
5
Order By: Relevance
“…In a qualitative study with 19 participants, Draffin et al . found that women reported an increase in risk perception and anxiety in response to the prescription of insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a qualitative study with 19 participants, Draffin et al . found that women reported an increase in risk perception and anxiety in response to the prescription of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between negative affect and risk perception may be particularly relevant in cases when women with GDM are prescribed glucose-lowering medication. In a qualitative study with 19 participants, Draffin et al [36] found that women reported an increase in risk perception and anxiety in response to the prescription of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of susceptibility or risk perception is prominent in theories and models of health behaviour change building upon or incorporating the Health Belief Model [36] and has also found its way into research on health behaviours in women with prior GDM [27,37]. Some women appear to simply not be aware of the long-term risk of Type 2 diabetes and/or have the understanding that their condition -GDMis now over and done with; wherefore, there is no need to worry about or contemplate future diabetes [33,38]. Qualitative studies have shed light on various perceptions about susceptibility in this group.…”
Section: Diabetes Beliefsmentioning
confidence: 99%
“…Qualitative studies from various countries have highlighted the importance of culturally appropriate diet recommendations for women from ethnic minority groups [33,34,38]. Women with GDM constitute a diverse group with characteristics such as age, BMI and ethnicity being important risk factors.…”
Section: The Healthcare Systemmentioning
confidence: 99%
“…They mentioned several advantages of the Pregnant+ app that could facilitate the care for those women. There is general agreement that efforts made to promote health need to be culture sensitive [39]. The Pregnant+ app involves features of the surface structure of culture-sensitivity as defined by Resnicow et al [40].…”
Section: Discussion Principal Resultsmentioning
confidence: 99%